Effects of dietary byproduct feeding withdrawal prior to market on finishing pig growth performance, carcass characteristics, carcass fat quality, intestinal weights, and economics - Coble, Kyle F.; DeRouchey, Joel M.; Tokach, Michael D.; Goodband, Robert D.; Dritz, Steven S.; Houser, Terry A.; Goehring, Brandon L.; Azain, M. J. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2014)
A total of 288 pigs (PIC 327 × 1050; initially 84.7 lb) were used in an 88-d study to determine the timing of high-fiber ingredient removal from the diet prior to marketing to optimize growth performance, carcass characteristics (primarily yield), carcass fatty acid composition, and economics. Two diet types, a corn-soybean meal control diet with low NDF (9.3%) and a high-fiber, high-NDF (19%) diet that contained 30% dried distillers grains with solubles (DDGS) and 19% wheat middlings (midds) were used throughout the study. Pens of pigs were randomly allotted to 1 of 6 dietary feeding strategies with 8 pigs per pen (4 barrows and 4 gilts) and 6 replications per treatment. The 6 feeding strategies consisted of the corn-soy control diet or high-fiber diet fed for the duration of the study, or the high-fiber diet fed until 20, 15, 10, or 5 d prior to slaughter after which the pigs were switched to the corn-soybean meal control diet. Overall (d 0 to 88), ADG was not affected by diet type or withdrawal strategy. Pigs fed the high-fiber diet continuously tended (P < 0.07) to have increased ADFI compared with pigs fed the control diet. This led to an increase (P < 0.01) in F/G for pigs fed the high-fiber diet for the entire study compared to pigs fed the control diet. The caloric efficiency of live weight gain of pigs fed the high-fiber diet continuously was worse (P < 0.03) compared with pigs fed the control diet throughout. Withdrawing the highfiber diet and switching to the control diet did not influence growth performance. For carcass characteristics, percentage yield and backfat were reduced (P < 0.01), whereas loin depth and jowl iodine value (IV) increased (P < 0.01) in pigs fed the highfiber diet continuously compared with those fed the corn-soybean meal control diet. As days of withdrawal from the high-fiber diet increased, percentage yield improved (linear; P < 0.01), whereas jowl IV decreased (linear; P < 0.01) and backfat increased (quadratic; P < 0.04). These data suggest that 15- to 20-d of removal from high-fiber diets prior to slaughter was optimal in terms of percentage carcass yield. The full pluck from pigs fed the high-fiber diet continuously tended to weigh more (P < 0.10) than from those fed the control diet. In addition, pigs continuously fed the high-fiber diet had heavier (P < 0.01) whole intestines, specifically full large intestines, than pigs fed the control. For pigs fed the high-fiber diet then switched to the corn-soy control, whole intestine weight tended to decrease (linear; P < 0.06) and full large intestine weight decreased (linear; P < 0.02) as withdrawal time increased. In summary, pigs fed the high-fiber diet had increased F/G, poorer caloric efficiency, and lower carcass yield compared with pigs fed the corn-soy control. Withdrawing pigs from the high-fiber diet and switching them to a corn-soy control diet did restore carcass yield when done for the last 15 to 20 d prior to harvest.
Keywords: Finishing pig; Fiber; Withdrawal; Growth performance